STUDY OF BIOFILM RESPONSE OF OLEA EUROPAEA TO UV RADIATIONS: AN IN VITRO APPROACH - I. Liaqat; N. M. Ali; S. A. Mirza; F. Ahsan; A. A. Sardar; H. M. Tahir; S. Ali; A. W. Qureshi; U. Haneef; nM. Ulfat (Journal of Animal and Plant Sciences, 2020)
A variety of bacteria, yeasts, and fungi colonize the aerial parts of plants termed as phyllosphere. Study of phylloshpere has gained considerable attention focusing on new non-invasive methods and bio-control agents of plant-associated microorganisms. The present study was designed to isolate microbes from phyllosphere of Olea europaea and assess their biofilm forming ability. Further, correlation between biofilm formation and ultraviolet (UV) radiation was observed. In total, four strains L1, L2, L3 and L4 were screened and purified from phyllosphere of O. europaea.  Biochemical characterization and 16srRNA sequencing identified these strains as Erwinia herbicola (MN905123), Micrococcus luteus (MN905159), Pseudomonas syringae (MN905161) and Bacillus subtilis (MN905164). Physiological characterization revealed that strains exhibited optimum growth at pH 7 and temperature 37°C. Biofilm formation showed B. subtilis as the strongest biofilm former. Afterwards, UV radiation at various time intervals i.e., 3, 4, and 15 minutes indicated that bacterial biofilm was resistant upto 10 minutes UV exposure. A significant decrease (p≤0.01) in biofilm formation of mutant strains was observed after 15 minutes UV exposure thus pointing towards significantly reduced activity of the DNA repair gene. This study provided evidence that environments exposed to desiccation and/ ambient UV radiations could principally select for highly resistant microbial biofilms organisms against ionizing radiations, enabling these to withstand extreme conditions.
Keywords: O. europaea; Phyllosphere; Biofilms; UV mutation; Pathogenic bacteria